Kvaliteter för högstadieskolgårdar : exemplet Strandängsskolan i Båstad - Hermander, Matilda (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2022)
The role of the school grounds is to support students’ health and development. Most of the research on school grounds focuses on pre- and primary school, while less is known about school grounds for adolescents. Without this knowledge, there is a risk that the perspectives of secondary school students get overlooked, or that the design solely is based on vague assumptions about their preferences. Strandängsskolan in Båstad is about to renew their school grounds, and one aim with the renewal process is to improve the outdoor environment for the secondary school students.